Acquired treatment response from neoadjuvant chemotherapy predicts a favorable prognosis for local advanced cervical cancer: A meta-analysis. Issue 17 (April 2018) - Zhu, Yunshan; Yang, Jianhua; Zhang, Xiao; Chen, Danxia; Zhang, Songying
Abstract: Background: Local advanced cervical cancer (LACC) is a considerable health crisis for women, and neoadjuvant chemotherapy (NACT) followed by radical surgery has been a suggested therapy method. However, the correlation between the tumor treatment response to NACT and the prognosis of LACC remains controversial. Methods: A comprehensive meta-analysis was performed to precisely assess the prognostic role of the clinical response and pathological response to NACT for LACC. The included studies were identified using PubMed and Web of Science up to July 2017. Hazard ratios (HR) and corresponding 95% confidence intervals (95% CI) for overall survival (OS) and disease-free survival (DFS) were determined using Review Manager (version 5.3) and Stata (version 12). Results: A total of 13 publications of 4727 cases were included. The treatment clinical response rate ranged from 58.49% to 86.54%, and the pathological response rate was 7.5% to 78.81%. Our combined results suggested that a clinical response was favorable for OS (HR=3.36, 95% CI: 2.41–4.69) and DFS (HR=2.36, 95% CI: 1.82–3.06). Further, a pathological response predicts favorable OS (HR=5.45, 95% CI: 3.42–8.70) and DFS (HR=3.61, 95% CI: 2.0–6.52). Conclusion: The response to NACT, including the clinical and pathological response, was associated with a favorable prognosis for patients with LACC. However, the predictive value of this factor in clinical practice warrants further in-depth research.